Cyber-Victimization and Emotional Intelligence as the Predictor of Cyberbullying in High School Students - Turnel Altan; Jale Eldeleklioğlu (Elementary Education Online, 2023)
The purpose of this study is to determine if cyber-victimization, emotional intelligence and its subdimensions predict cyberbullying in high school students. The population includes 146 female (57%) and 110 male (43%), a total of 256, 9th graders. Research data was collected using Cyber Victim and Bullying Scale (CVBS) and BarOn Emotional Intelligence Inventory. Furthermore, Pearson correlation coefficient and multiple linear regression analysis were used in data analysis. The results of the analyses showed that cyber-victimization, interpersonal relationships, social conformity, general mood and coping with stress are statistically significant predictors of cyberbullying. It was further found that cybervictimization and interpersonal relationships are the most significant predictors of cyberbullying, while it was found that variables such as social conformity, general mood and coping with stress are not statistically significant predictors of cyberbullying.